Systematic review of Late Jurassic sauropods from the Museu Geológico collections (Lisboa, Portugal) - Mocho, Pedro; Royo-Torres, Rafael; Malafaia, Elisabete; Escaso, Fernando; Ortega, Francisco (Journal of Iberian Geology, 2016)
The Museu Geológico collections house some of the first sauropod references of the Lusitanian Basin Upper Jurassic record, including the Lourinhasaurus alenquerensis and Lusotitan atalaiensis lectotypes, previously considered as new species of the Apatosaurus and Brachiosaurus genera, respectively. Several fragmentary specimens have been classical referred to those taxa, but the most part of these systematic attributions are not supported herein, excluding a caudal vertebra from Maceira (MG 8804) considered as cf. Lusotitan atalaiensis. From the material housed in the Museu Geológico were identified basal eusauropods (indeterminate eusauropods and turiasaurs) and neosauropods (indeterminate neosauropods, diplodods and camarasaurids and basal titanosauriforms). Middle caudal vertebrae with lateral fossae, ventral hollow border by pronounced ventrolateral crests and quadrangular cross-section suggest for the presence of diplodocine diplodocids in north area of the Lusitanian Basin Central Sector during the Late Jurassic. A humerus collected from Praia dos Frades (MG 4976) is attributed to cf. Duriatitan humerocristatus suggesting the presence of shared sauropod forms between the Portugal and United Kingdom during the Late Jurassic. Duriatitan is an indeterminate member of Eusauropoda and the discovery of new material in both territories is necessary to confirm this systematic approach. The studied material is in according with the previous recorded paleobiodiversity for the sauropod clade during the Portuguese Late Jurassic, which includes basal eusauropods (including turiasaurs), diplodocids and macronarians (including camarasaurids and basal titanosauriforms).